(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2019)
The paper aims to investigate if and how social media platforms made users change their political opinions, particularly regarding the hot topic: nationalism vs. globalism. Social networks allow people to talk to each other all over the world, creating a non-stop global conversation. These kinds of media are global by nature and we are used to seeing them as one of the many consequences of globalization. In spite of this feature a paradoxical effect has occurred, as today social media are the privileged platforms for nationalist organizations, promoting the idea of the nation (or the return to) as the best way to fight globalisation. The paper, through a narrative approach, investigates nationalism on social media and its possible effects. The paper assesses scientific articles from international literature in English. The review also covers journalistic articles, reporting data, insights or simple news regarding the subject. In this case, the paper includes only articles coming from mainstream publications. Trying to pursue this objective, the review excludes articles not clearly reporting the name of the publication, author and date. In addition to this, all these articles are checked, making sure they have been cited or linked by other mainstream media.